Hubungan Antara Derajat Osteoartritis Genu Dengan Indeks Massa Tubuh: Studi Berbasis Radiografi Konvensional Lutut Berdasarkan Kriteria Kellgren & Lawrence - Airlangga Archimedes Gymnastiar; Winansih Gubali; Abdi Dzul Ikram Hasanuddin; Sri Manovita Pateda; Elen Mahmud Lukum (Journal of Innovative and Creativity, 2026)
Background: Knee osteoarthritis (OA) is a common degenerative joint disease characterized bycartilage damage, osteophyte formation, and joint space narrowing. Body Mass Index (BMI) is apotential risk factor influencing OA severity by increasing mechanical load on the knee joint. Kellgren& Lawrence classification via conventional radiography is a standard method to assess OA severity.Objective: This study aimed to analyze the association between BMI and knee OA severity based onKellgren & Lawrence criteria. Methods: An analytic observational cross-sectional study wasconducted at RSUD Prof. Dr. Aloei Saboe from May to July 2025. Thirty patients diagnosed withknee OA underwent BMI measurement and conventional knee radiography. Data were analyzed usingSpearman rank correlation test. Results: Most patients had Kellgren & Lawrence grade 2 or 3 OA.BMI distribution ranged from normal to severe obesity. Statistical analysis showed no significantcorrelation between BMI and OA severity (p = 0.457). Conclusion: No significant associationbetween BMI and radiographic OA severity was found. Further studies with larger samples arerecommended.